2011
DOI: 10.1177/1363461511425622
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking cultural competence: Insights from indigenous community treatment settings

Abstract: Multicultural professional psychologists routinely assert that psychotherapeutic interventions require culturally competent delivery for ethnoracial minority clients to protect the distinctive cultural orientations of these clients. Dominant disciplinary conceptualizations of cultural competence are "kind of person" models that emphasize specialized awareness, knowledge, and skills on the part of the practitioner. Even within psychology, this approach to cultural competence is controversial owing to profession… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 55 publications
1
82
0
Order By: Relevance
“…Transcultural Psychiatry 52 (2) and Gone (2012), who argued that this approach is unlikely to yield useful cultural information, we actually found the opposite. For example, a White female primary care physician we interviewed strongly resisted documents instructing clinicians to use the "ethnic food pyramid" when evaluating the dietary habits of her patients.…”
mentioning
confidence: 50%
See 1 more Smart Citation
“…Transcultural Psychiatry 52 (2) and Gone (2012), who argued that this approach is unlikely to yield useful cultural information, we actually found the opposite. For example, a White female primary care physician we interviewed strongly resisted documents instructing clinicians to use the "ethnic food pyramid" when evaluating the dietary habits of her patients.…”
mentioning
confidence: 50%
“…Wendt and Gone argue that this approach, which effectively counters the tendency to overessentialize and improperly apply group-based cultural characteristics to individual patients who depart from group norms, "may come at the cost of the ability to identify any culturally distinctive tactics or strategies at all" (2012, p. 210). Wendt and Gone's (2012) strategy to combat this polarity is to question the cultural neutrality of the process-oriented approach and to explore innovative, locally controlled treatment programs in indigenous community settings as an alternative way of examining the cultural problematic present in medical encounters. By focusing on real-world cases of treatment modalities and interventions, they found that many putatively emic treatment modalities actually are a hybrid combination of general psychotherapeutic practice and locally determined, culturally tailored treatment.…”
mentioning
confidence: 99%
“…42 For many Indigenous patients, the legacies of colonization have left a deep epistemological chasm that cannot be easily traversed by health care professionals, no matter how well intended or culturally competent. 43 Participants repeatedly emphasized the importance of shared histories of colonial oppression as a "common ground" for building trust and openness with the Elders, enabling them to establish therapeutic alliances they had not previously experienced with health care providers. In this way, relational experiences of trust with the Elders seemed to lessen epistemic mistrust that previously acted as an obstacle to care.…”
Section: Discussionmentioning
confidence: 99%
“…This notion has been taken up by indigenous health researchers, planners and advocates in Canada and extended to provide a general model for improving the quality of health care [90][91][92]. Research is needed to identify when and how particular models of service and modes of clinical intervention improve access to care, the clinical alliance, and outcomes for specific groups [93].…”
Section: Cultural Competence Safety and Efficacymentioning
confidence: 99%